Failure analysis on fully-transparent deep-sea pressure hulls used at 2,500 m depth - Wu, Yu; Li, Youjie; Luo, Ruilong; Zhang, Zhonggang; Wang, Fang; Zhao, Bingxiong; Yang, Chao; Zhang, Jinfei; Gaidai, Oleg (Frontiers in Materials, 2023)
Fully-transparent deep-sea pressure hulls have been attracted attention in recent years with the increasing demand for underwater observation. So far, public researches on design rule and failure modes for fully-transparent deep-sea pressure hulls are limited and the relevant experience cannot meet the requirements of new cabin design. In this study, the compression test is carried on, in which the material samples are subjected to quasi-static compressive load until failure in tests at different loading rates, and the hyperelastic finite element model is established in LS-DYNA software to simulate the failure process. Simulation results of material properties in finite element analysis on the cylindrical samples are compared with the experimental data, including the characteristic points of the mechanical properties in elastic stage and hardening stage, the ultimate load and failure mode of the samples. Mesh convergence analysis is conducted, and the appropriate mesh quality is accordingly selected in simulation of fully-transparent deep-sea pressure hulls. An equation for prediction of instability-type failure is described, which is derivation based on the classical analytical expression of elastic instability, thus, when 5 times of safety factor is taken, the wall thickness of the pressure hull is calculated to be t/R0 = 0.0685 at 2,500 m depth. Ultimate strength and failure mode of a typical fully-transparent deep-sea pressure hull are simulated. First, the first-order linear buckling modal analysis is carried out to simulate initial geometric imperfections. Then, simulations for the loading and collapse process of two fully-transparent pressure hulls respectively with one opening and two openings are conducted, and the ultimate load of 126 MPa and 128 MPa for the two kinds of hulls are obtained. Finally, simulation of a scaled pressure hull is carried out and simulation results are compared with the experimental data in reference, which are basically consistent. The calculated failure strength shows that the spherical hulls satisfy the safety factor requirement of 5 times. The provided simulation procedure can be referred for failure analysis of fully-transparent pressure hulls.